2005
DOI: 10.1002/hlca.200590020
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviors of Metal Acetylides with Dinitrogen Tetroxide

Abstract: Lithium phenylacetylide (1a) and N 2 O 4 (2) at À 788 yield diphenylbutadiyne (6a) by oxidative coupling, phenylacetylene (7a) by oxidation and then solvent H-abstraction, and benzoyl cyanide (8) by dimerizativerearrangement of nitroso(phenyl)acetylene (23). Nitro(phenyl)acetylene (3, R Ph) is not obtained. Benzonitrile (9), a further product, possibly results from hydrolytic decomposition of nitroso(phenyl)ketene (27) generated from phenylacetylenyl nitrite (26). Phenylacetylene (7a) and 2 give, along with (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 69 publications
0
11
0
1
Order By: Relevance
“…Moreover, we found that the oxidative homocoupling of vinyl Grignard reagents to provide dienes is possible with TEMPO: b-Styrylmagnesium chloride and C 6 H 13 CH=CHMgCl were transformed into the dienes 1 k and 1 l, respectively ( Table 1, entries 15 and 16). Alkynyl magnesium compounds also underwent TEMPO-mediated coupling; [6] however, longer reaction times (4-6 h) were necessary. At room temperature, the homocoupling of C 6 H 5 CCMgBr was very slow ( Importantly, we found that TEMPO-MgBr (2), which was formed as a by-product, was reoxidized readily to TEMPO with dioxygen in refluxing THF within 10 min, as indicated by TLC [Eq.…”
Section: Modhu Sudan Maji Thorben Pfeifer and Armido Studer*mentioning
confidence: 99%
“…Moreover, we found that the oxidative homocoupling of vinyl Grignard reagents to provide dienes is possible with TEMPO: b-Styrylmagnesium chloride and C 6 H 13 CH=CHMgCl were transformed into the dienes 1 k and 1 l, respectively ( Table 1, entries 15 and 16). Alkynyl magnesium compounds also underwent TEMPO-mediated coupling; [6] however, longer reaction times (4-6 h) were necessary. At room temperature, the homocoupling of C 6 H 5 CCMgBr was very slow ( Importantly, we found that TEMPO-MgBr (2), which was formed as a by-product, was reoxidized readily to TEMPO with dioxygen in refluxing THF within 10 min, as indicated by TLC [Eq.…”
Section: Modhu Sudan Maji Thorben Pfeifer and Armido Studer*mentioning
confidence: 99%
“…15,16). Auch Alkinylmagnesiumverbindungen ließen sich mit TEMPO unter Homokupplung umsetzen 6. Allerdings waren hierzu längere Reaktionszeiten erforderlich (4–6 h).…”
Section: Methodsunclassified
“…8,9 In 1996, Woltermann et al treated a host of phenylacetylides with various nitrating agents in a futile attempt at creating 7 (Scheme 7). 16,54 One should note that Schmitt had already remarked in 1987 that 'addition of nitronium One of the serendipitous outcomes of these experiments when employing dinitrogen tetroxide with (phenylethynyl)lithium (38), (phenylethynyl)zinc bromide (39), and (phenylethynyl)magnesium bromide (40) was an interesting oxidative coupling to diphenylbutadiyne (41). This process involves a likely initial one-electron oxidation to the phenylethynyl radical, a notion supported by the observation of hydrogen abstraction from the solvent to give varying amounts of phenylacetylene (42).…”
Section: Scheme 5 Failure Of Nitronium Tetrafluoroborate To Nitrate Smentioning
confidence: 99%
“…Some examples are shown in Scheme 8. 16,54 Scheme 8 One-electron oxidation of metal phenylacetylides by dinitrogen tetroxide Despite the litany of failures summarized in this section, the nitration of alkynes, in particular certain stannyl and silyl derivatives, constitutes one of the most effective entries into the class of nitroalkynes (see section 4.2.1).…”
Section: Scheme 5 Failure Of Nitronium Tetrafluoroborate To Nitrate Smentioning
confidence: 99%
See 1 more Smart Citation